Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Kinerja Karyawan; Literature Review - Radiva Dianda Zahra Putri; Sherly Yulianti; M. Isa Anshori (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
A good working environment contributes to improved employee performance. Factors such as ability, motivation, leadership, team, system and contextual have been shown to influence employee performance. Through a review of the literature, the purpose of this study is to gain a better understanding of this topic. Previous studies show how organizational culture, leadership style, work environment, work motivation, and organizational commitment to employee performance. An organizational culture that supports teamwork, innovation, fairness, and transparency, along with a leadership style that is inspiring, empowering, and adaptive, has a significant positive impact on employee performance. The combination of these two factors can create an ideal work environment for performance, but other factors, such as interpersonal communication, training and motivation, also need to be considered. A strong organizational culture and effective leadership can increase employee motivation, commitment and loyalty, which will ultimately impact the product.